High glucose induction of DNA-binding activity of the transcription factor NFκB in patients with diabetic nephropathy - Yang, Bingmei; Hodgkinson, Andrea; Oates, Peter J.; Millward, Beverley A.; Demaine, Andrew G. (Biochimica et biophysica acta. Molecular basis of disease, 2008)
The aim of this study was to investigate whether high glucose induces aldose reductase (AKR1B1) expression through NFκB, which may contribute to the pathogenesis of diabetic nephropathy. 34 Caucasoid patients with type 1 diabetes were recruited; 20 nephropaths and 14 long-term uncomplicated subjects. Peripheral blood mononuclear cells (PBMCs) were cultured under normal or high glucose (25 mmol/l of d-glucose) with or without an aldose reductase inhibitor (ARI). High glucose increased NFκB binding activities in the PBMCs from nephropaths compared to the uncomplicated subjects (1.77 ± 0.22 vs. 1.16 ± 0.04, p = 0.02). ARI induced a substantially greater decrease of NFκB binding activities in the nephropaths compared to the uncomplicated subjects (0.58 ± 0.06 vs. 0.79 ± 0.06, p = 0.032). AKR1B1 protein levels in the nephropaths were increased under high glucose conditions and decreased in the presence of an ARI, whilst the silencing of the NFκB p65 gene in vitro reduced the transcriptional activities of AKR1B1 in luciferase assays. These results show that NFκB induces AKR1B1expression under high glucose conditions, and the pattern of expression differs between nephropaths and the uncomplicated subjects.